A target rate for resuscitation attempted by bystanders for patients experiencing out-of-hospital cardiac arrest in China - Wang, Y M; Hou, L; Feng, X F; Quan, K Y; Chen, G X (Zhōnghuá xīnxuèguănbìng zázhi, 2025)
To explore an initial target rate for resuscitation attempted by bystanders for patients experiencing out-of-hospital cardiac arrest in China. We searched seven electronic databases, including CNKI, VIP, Wanfang, CBM, PubMed, Cochrane, EMBase, for Utstein-style reports of out-of-hospital cardiac arrest, containing data on bystander resuscitation and survival to discharge or 30 days after arrest. All patients with cardiac arrest diagnosed at prehospital emergency medical services were included. Meta-analysis was performed to pool rate ratios (RR) with 95% confidence intervals (CI) of the rate of survival to discharge or 30 days. The population attributable risk percent (PARP) was calculated with RR, and the growth rate curve of PARP following bystander cardiopulmonary resuscitation rate was plotted. We established a multiple linear regression model to show the change in survival to discharge or 30 days with increasing rates of resuscitation attempted by bystanders. We included 24 cohorts with 279 641 patients